Rhetoric, scripture and theology: essays from the 1994 Pretoria Conference - Porter, Stanley E. (Journal for the study of the New Testament / Supplement series, 1996)
Rhetoric, Scripture and Theology aptly describe the contents of this collection of essays from the 1994 Pretoria Rhetoric Conference. The conference marked a significant dialogue among scholars gathered from many nations to consider how rhetoric engages with the study of scripture and theology. South Africa provided a suitable context for such discussion. Although the contributors are not only from South Africa, the addressing of issues pertinent to a South African context shows through in many of the essays. Those that do not address particularly South African issues raise equally important issues regarding the topic of rhetoric and its relation to contemporary theological discourse.